2023
DOI: 10.1093/pnasnexus/pgad055
|View full text |Cite
|
Sign up to set email alerts
|

cAMP controls the balance between dormancy and activation of primordial follicles in mouse ovaries

Abstract: In mammalian ovaries, the balance between dormancy and activation of primordial follicles determines the female fecundity and endocrine homeostasis. Recently, several functional molecules and pathways have been reported to be involved in the activation of primordial follicles. However, the homeostasis regulatory mechanisms of primordial follicle activation are still scant. Our previous study has proved that a relatively higher concentration of cyclic AMP (cAMP) is required for primordial follicle formation. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…We found that ADCY3 (adenylate cyclase 3) is an activator of cAMP. Increased expression of ADCY3 can catalyze ATP to generate cAMP, which then binds to the regulatory subunits of PKA, activating the catalytic subunits of PKA and subsequently activating PKA ( Hong et al, 2013 ; Zheng et al, 2023 ). Therefore, regulating the activity of cAMP plays a crucial role in controlling the excitability of neurons and networks ( Zhang et al, 2021b ).…”
Section: Resultsmentioning
confidence: 99%
“…We found that ADCY3 (adenylate cyclase 3) is an activator of cAMP. Increased expression of ADCY3 can catalyze ATP to generate cAMP, which then binds to the regulatory subunits of PKA, activating the catalytic subunits of PKA and subsequently activating PKA ( Hong et al, 2013 ; Zheng et al, 2023 ). Therefore, regulating the activity of cAMP plays a crucial role in controlling the excitability of neurons and networks ( Zhang et al, 2021b ).…”
Section: Resultsmentioning
confidence: 99%
“…3, I – N ). We further investigated the effect of ROCK1 on follicular development using a model of ovarian topical administration in vivo ( 21 , 22 ). The ovaries of 3-wk-old mice were given local in vivo injections of matrigel containing Y-27632, and ovaries were collected 2 wk after injection ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Typical ovarian administration was performed according to the previous report ( 21 , 22 ). Briefly, 3-wk-old CD-1 female mice were anesthetized with avertin (300 mg/kg, T48402, Sigma), and the ovaries were gently exposed from the incisions on the backs, as illustrated in Supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Other factors playing essential roles in primordial follicle activation and follicular reserve maintenance include pre-granulosa cell-driven factors, such as KIT Ligand (KITL), mechanistic target of rapamycin kinase (mTOR), forkhead box l2 (FOXL2), SMAD family member 3 (SMAD3) and WNT [20][21][22][23]. Also, participation of cyclin dependent kinase inhibitor 1B (CDKNIB), HIPPO, nerve growth factor (NGF), transforming growth factor-beta (TGF-β), Rhoassociated coiled-coil containing protein kinase 1 (ROCK1), cyclin AMP (cAMP), and Sirtuin 1 (SIRT1) has been reported in primordial follicle activation and reserve maintenance [24][25][26][27][28][29][30][31][32].…”
Section: Ivyspring International Publishermentioning
confidence: 99%